Against show culture: universal priesthood and active participation. Pastoral learnings from Comunidad Luterana Santísimo Redentor and Comunidad Luterana del Perú - Suárez Arispe, Carola (2023)
The different masses, cults, services have reproduced to a greater or lesser extent an ecclesiology that is the result of processes prior to the pandemic, so participation in cyberspace has not necessarily paid for in structural changes. The gaze of the laity, the clergy or the sacraments have found a continuity in cyberspace that has not exactly been questioned. Participation in the virtual world does not mean an achievement, but it would rather be a colonization of a space in which, in other circumstances, they would not have taken any steps, so the visibility of certain bodies sustains an institutionality that promotes show culture.